Morphological Study for Identification Improvement of Tambra Fish (Tor spp.: Cyprinidae) from Indonesia - HARYONO HARYONO; AGUS HADIAT TJAKRAWIDJAJA (Biodiversitas Journal of Biological Diversity, 2006)
The identification improvement among species of Tor was conducted based on fish specimens in Museum Zoology Bogor. Each species represented 8 specimens and measured 22 characters (in mm) used digital caliper. The Canonical variate analysis (discriminant function analysis) was used. The results showed these four species different in morphology, and Tor soro 100% grouping from its congeners. Five characters were selected to separate species. Commonly, population of tambra fish in the world was critical therefore needed conservation. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Keywords: fish, Tor, morphology, character, species, conservation